Analisis Isi Mengenai Kesehatan Jiwa Dalam Podcast Raditya Dika Di Media Sosial Youtube - Arfian Suryasuciramdhan; Risti Septyani; Ika Choirunnissa; Fadiah Cahya Amelia; Mario Maulana (Student Scientific Creativity Journal, 2024)
This study is qualitative, with one interviewee. The results of this study show that the podcast audience of Raditya Dika's YouTube account has sufficient thoughts and a good understanding of the various mental health issues discussed by Dr Jiemi Ardian, SpKJ. Mental health in each individual cannot be generalised. This condition makes the urgency of mental health discussions that lead to how to empower individuals, families, and communities to be able to find, maintain, and optimise their mental health conditions in dealing with everyday life. The knowledge and behaviour of most viewers of YouTube account users who can pay attention to all information through digital media, where most of them are Raditya Dika's YouTube subscribers who are relatively young. This study aims to determine the content of mental health content messages on Raditya Dika's YouTube account. What is expected from this content is that the audience can care about anticipating and preventing triggers for mental health disorders.